Kajian Kritis Penerapan Akuntansi Sumber Daya Manusia - Wildatul Muawanah; Iklimah Putry Murady; Gideon Setyo Budiwitjaksono (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the treatment of the implementation of human resource accounting in Indonesia. In fact, it is human resource accounting that has great concern because the treatment has not been determined by Bapepam-LK. The application of ASDM is an acknowledgment that humans are users who are recognized as capital or assets. The method used in this study is a literature review which is the result of an analysis of articles that have gone through the Mendeley database. From the articles reviewed as many as 12 articles, it shows that the contribution in the application of human resource accounting, both companies and institutions, has a positive impact on improving company performance. However, not many companies in Indonesia have used HR in their financial reporting. Keywords: Application, confession, Human resource accounting, measurement.